Pendidikan Diniyah Formal Wajah Baru Pendidikan Pesantren Untuk Kaderisasi Ulama’ - Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2016)
The development of education, especially Islamic education in Indonesia have ups and downs. In the early period of Islamic education are dominated by typical salaf pesantren education. Pesantren education emphasizes the mastery of Islamic studies in depth. These studies are made directly to the Islamic treasury in the form of the book in Arabic. This is what arise to the study of the yellow book. According to experts, the lack of a typical Islamic studies schools lies in a dialectic with modern science, especially in the scientific methodology. The solution offered in the form of an integrated Islamic studies between education schools and scientific education. Thus was born the model schools Government Elementary School, MTs, and Madrasah Aliyah to Islamic High School or Institute for Islamic Studies. School integrative model of early development is quite promising. However, the longer school integrative model is considered a shift from the original purpose. In fact, many students and school products integrative model results do not meet expectations. Students and school leavers integrative model is not much different than public school graduates. This then raises its own anxiety over the fate of studies and Islamic education. Regeneration Ulama 'the main purpose of Islamic studies to be neglected. Here, then, Diniyah Formal Education as an alternative to the model of Islamic studies salaf pesantren education and integrative education model. With hope, graduates become mutafaqqih fid-din, deep in the typical Islamic studies pesanten, scientists intellect, berakhlaqul karimah and insightful moderate.